Language of Instruction as a Limiting Factor in Learner Participation in the Classroom - Netshivhumbe, Ndivhuwo Prudence (CV Sinergi Ilmu dan Publikasi, 2025)
This study explored the role of the language of teaching and learning as a limiting factor in learner participation at selected schools in the Vhembe district. This research utilized an interpretative qualitative approach; the research involved physical science teachers and learners from three schools. Data were collected through classroom observations. The findings revealed that the use of English as the medium of instruction in physical science hindered both classroom interaction and discourse. Limited interaction was observed between teachers and learners, as well as among learners themselves, due to the use of a language that was neither the teachers' nor the learners' first language. As a result, learners struggled to engage fully in class activities because they did not completely understand the language of instruction. Additionally, the language barrier hindered their ability to grasp scientific concepts, ask questions, and participate in discussions. Based on these findings, the study recommends the development of teaching and learning materials in African indigenous languages to improve learner participation and performance. Furthermore, it advocates for the use of a language that both teachers and learners are comfortable with to enhance teaching and learning outcomes. The study highlighted how the language of instruction impacts learners' learning, while also suggesting ways to advocate for change.